2011
DOI: 10.1016/j.pupt.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties, lung deposition modeling, and bioactivity of recombinant GM-CSF aerosolised with a highly efficient nebulizer

Abstract: Pulmonary alveolar proteinosis (PAP) is a rare condition characterized by the accumulation of lipoproteinaceous material within air spaces. Although whole lung lavage is the current standard of care, recent advances in our understanding of PAP pathophysiology suggest that the disorder may benefit from inhalation of recombinant granulocyte-macrophage colony-stimulating factor (rGM-CSF). The aim of this study was to determine the physical properties and bioactivity of rGM-CSF aerosolized by the highly efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In an apparatus which combines a vibrating mesh nebulizer with a computerized compressor controlling both inhalation fl ow rate and inhaled volume [13]. A 12 weeks acute phase (daily single dose of 250 mcg, for 5 days per week) was followed by a 6 months chronic phase (250 mcg/day on 2 consecutive days every 2 weeks), which started one month after the end of the acute phase.…”
Section: Case Reportmentioning
confidence: 99%
“…In an apparatus which combines a vibrating mesh nebulizer with a computerized compressor controlling both inhalation fl ow rate and inhaled volume [13]. A 12 weeks acute phase (daily single dose of 250 mcg, for 5 days per week) was followed by a 6 months chronic phase (250 mcg/day on 2 consecutive days every 2 weeks), which started one month after the end of the acute phase.…”
Section: Case Reportmentioning
confidence: 99%
“…A previous report by Luisetti et al 127 showed that the AKITA2 APIXNEB nebulizer system aerosolized 96% of a recombinant GM-CSF filling dose, and based on the International Commission on Radiological Protection (ICRP) deposition models, it was predicted that 80.4% of the filling dose would deposit in the lungs. No studies have been performed that compare the AKITA2 APIXNEB nebulizer system and the PARI LC Plus nebulizer used in the previous studies to treat pulmonary alveolar proteinosis.…”
Section: Granulocyte-macrophage Colony-stimulating Factormentioning
confidence: 99%
“…49 These were also the operating principles of the AKITA JET and AKITA2 APIXNEB (Vectura, Wilshire, United Kingdom). 49,50 The system has a 4-mL reservoir and allows targeting of peripheral or central airways by modifying the time of release of the aerosol during the inspiratory phase. Aerosol release at the beginning of the inhalation will result in more distal deposition, whereas release in the middle of the inhalation will result in more central deposition.…”
Section: Nebulizermentioning
confidence: 99%